Integration of GaN analog building blocks on p-GaN wafers for GaN ICs. (February 2021) - Li, Xiangdong; Geens, Karen; Amirifar, Nooshin; Zhao, Ming; You, Shuzhen; Posthuma, Niels; Liang, Hu; Groeseneken, Guido; Decoutere, Stefaan
Abstract: We demonstrate the key module of comparators in GaN ICs, based on resistor-transistor logic (RTL) on E-mode wafers in this work. The fundamental inverters in the comparator consist of a p-GaN gate HEMT and a 2DEG resistor as the load. The function of the RTL comparators is finally verified by a undervoltage lockout (UVLO) circuit. The compatibility of this circuit with the current p-GaN technology paves the way for integrating logic ICs together with the power devices.